2000
DOI: 10.1128/jb.182.9.2520-2529.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Trimethylamine Methyltransferase Gene and Multiple Dimethylamine Methyltransferase Genes of Methanosarcina barkeri Contain In-Frame and Read-Through Amber Codons

Abstract: Three different methyltransferases initiate methanogenesis from trimethylamine (TMA), dimethylamine (DMA) or monomethylamine (MMA) by methylating different cognate corrinoid proteins that are subsequently used to methylate coenzyme M (CoM). Here, genes encoding the DMA and TMA methyltransferases are characterized for the first time. A single copy of mttB, the TMA methyltransferase gene, was cotranscribed with a copy of the DMA methyltransferase gene, mtbB1. However, two other nearly identical copies of mtbB1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
126
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 48 publications
6
126
0
1
Order By: Relevance
“…mazei mtbC 1 , mttB 1 , mttC 1 , mttP, and mtbB 1 (MM 1687 to MM 1694) have been shown to form a transcriptional unit (K. Veit and R. A. Schmitz, unpublished), which is in accordance to the genomic organization in M. barkeri (15). Thus, in the following experiments the mttB 1 gene was exemplarily investigated for the regulation of the complete operon encoding DMA and TMA methyltransferase 1, their corresponding corrinoid proteins, and a potential TMA permease.…”
Section: Fig 1 Operons Encoding Methylamine Methyltransferases In Mmentioning
confidence: 50%
See 4 more Smart Citations
“…mazei mtbC 1 , mttB 1 , mttC 1 , mttP, and mtbB 1 (MM 1687 to MM 1694) have been shown to form a transcriptional unit (K. Veit and R. A. Schmitz, unpublished), which is in accordance to the genomic organization in M. barkeri (15). Thus, in the following experiments the mttB 1 gene was exemplarily investigated for the regulation of the complete operon encoding DMA and TMA methyltransferase 1, their corresponding corrinoid proteins, and a potential TMA permease.…”
Section: Fig 1 Operons Encoding Methylamine Methyltransferases In Mmentioning
confidence: 50%
“…This analysis showed that the observed changes in expression of the mtmBC operons during lag-or stationary-phase growth compared to exponential- Transcription of pyl genes does not appear to be affected by nitrogen limitation and the presence of TMA. All methylamine methyltransferase transcripts possess an internal amber codon (UAG) (15), which encodes the recently discovered amino acid pyrrolysine (12,19). Thus, synthesis of functional methylamine methyltransferases is dependent on the expression of the pyl genes, whose gene products are responsible for the synthesis of pyrrolysyl-tRNA Pyl .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations